Implikasi Praktek Total Quality Management (TQM) terhadap Daya Saing, Kepuasan Konsumen, dan Kinerja Bisnis pada Perusahaan Manufaktur di Kota Makassar - Ramlawati -; Surachman -; Djumilah Zain; Djumahir - (Jurnal Aplikasi Manajemen, 2012)
This research was conducted in the manufacturing industry in the municipality of Makassar. Data was collected using questionnaire using Likert scale. Respondents were asked to report their perception on the application of TQM practices, competitiveness, consumer satisfaction and business performance. The hypothesis for this research was tested using path analysis. The result of this research shows that proper TQM practices can improve competitiveness, consumer satisfaction and business performance. Despite the fact that competitiveness does not directly impact business performance, but competitiveness can improve business performance indirectly through consumer satisfaction. This means that competitivenesss can have better impact when the company can improve its consumer satisfaction as a result of better implementation of TQM practices.Keywords: TQM practices, competitiveness, consumer satisfaction, business performance